Managing Whiteflies on Landscape Ornamentals - Eileen A. Buss; Catherine M. Mannion; Lance S. Osborne; Adam G. Dale (EDIS)
Whiteflies are a common pest of many ornamental plants throughout Florida and the world. There are more than 1,500 species worldwide and over 75 reported in Florida. Some of the most economically important species in Florida are the sweetpotato whitefly, also called the silverleaf whitefly (Bemisia tabaci), the ficus whitefly (Singhiella simplex), and the citrus whitefly (Dialeurodes citri). Although infestation does not always require treatment, it is important to be able to identify and monitor for these pests for effective integrated pest management. This 8-page fact sheet describes whitefly species, their identification and biology, the damage they cause, and best management practices to control them and still maintain healthy populations of natural enemies and other beneficial insects.